2020
DOI: 10.5539/sar.v9n2p30
|View full text |Cite
|
Sign up to set email alerts
|

Technical Efficiency of Moringa Production: A case Study in Wolaita and Gamo Zones, Southern Ethiopia

Abstract: Moringa has been becoming among vastly growing and trading commodities in different parts of Ethiopia for its multiple benefits. However, empirical researches analyzing its productivity at smallholder farmer level were missing. This study aimed to fill the existing gap with a cross-sectional survey study on sampled 117 Moringa producer farmers from southern Ethiopia. The Stochastic Frontier Model was used to estimate the level and factors determining the technical efficiency of Moringa production. The collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…The link between efficiency and landholding size has been the subject of much discussion in the literature. While several studies found that small farmland size increases inefficiency due to simple management and intensive resource use in comparison to larger land size, our finding conforms with the results reported by Haji (2008), Debebe et al (2015), and Tafesse et al (2020).…”
Section: Sources Of Inefficienciessupporting
confidence: 92%
“…The link between efficiency and landholding size has been the subject of much discussion in the literature. While several studies found that small farmland size increases inefficiency due to simple management and intensive resource use in comparison to larger land size, our finding conforms with the results reported by Haji (2008), Debebe et al (2015), and Tafesse et al (2020).…”
Section: Sources Of Inefficienciessupporting
confidence: 92%
“…The link between efficiency and landholding size has been the subject of much discussion in the literature. While several studies found that small farmland size increases inefficiency due to simple management and intensive resource use in comparison to larger land size, our finding conforms with the results reported by Haji (2008), Debebe et al (2015), and Tafesse et al (2020).…”
Section: Sources Of Inefficienciessupporting
confidence: 92%